Hubungan Beban Kerja Dan Lama Kerja Dengan Tingkat Stres Guru SMK Sekolah Menengah Teknologi Industri (SMTI) Makassar (Window of Public Health Journal, 2025)
Teacher stress is an experience experienced by teachers including unpleasant emotions, negative emotions, such as: anger, anxiety, pressure, frustration or depression as a result of various aspects of work as a teacher. This study aims to determine the relationship between workload and length of work with the stress level of SMK Makassar Industrial Technology Middle School teachers. This type of research is a quantitative study with a cross sectional study approach. The population of this study was 50 teachers who worked using the total sampling method. Data collected by questionnaire. Methods of data analysis using univariate analysis and bivariate data were analyzed using the chi-square test at the confidence level (α = 0.05). The results of this study indicate that between workload (p = 0.004) and length of work (p = 0.939) with the stress level of teachers of SMK Industrial Technology Middle School Makassar. The conclusion is that there is a relationship between workload and stress levels and there is no relationship between length of work and the stress level of SMK SMTI Makassar teachers. So it is advisable to make the best use of rest time.